Flow characteristics and alkalinity of novel bioceramic root canal sealers - Anastasios Katakidis; Konstantinos Sidiropoulos; Elisabeth Koulaouzidou; Christos Gogos; Nikolaos Economides (Restorative Dentistry & Endodontics, 2020)
ObjectiveThis study aimed to examine the physical properties (pH and flow) of 2 novel bioceramic sealers.Materials and MethodsThe tested sealers were a calcium hydroxide sealer (Sealapex) and 2 bioceramic sealers (BioRoot RCS and TotalFill BC Sealer). Flow measurements were conducted according to ISO 6876/2012, with a press method of 0.05 mL of sealer. The pH of fresh samples was tested immediately after manipulation, while set samples were stored for 3 times the recommended setting time. The predetermined time intervals ranged from 3 minutes to 24 hours for fresh samples and from 10 minutes to 7 days and 4 weeks for the set samples. Analysis of variance was performed, with p = 0.05 considered indicating significance.ResultsThe mean flow values were 26.99 mm for BioRoot, 28.19 for Sealapex, and 30.8 mm for TotalFill BC Sealer, satisfying the ISO standard. In the set samples, BioRoot RCS had higher pH values at 24 hours to 1 week after immersion in distilled water. At 2 weeks, both bioceramic sealers had similar pH values, greater than that of Sealapex. In the fresh samples, the bioceramic sealers had significantly higher initial pH values than Sealapex (p < 0.05). At 24 hours post-immersion, all sealers showed an alkaline pH, with the highest pH observed for TotalFill.ConclusionsThe TotalFill BC Sealer demonstrated the highest flow. The bioceramic sealers initially presented higher alkaline activity than the polymeric calcium hydroxide sealer. However, at 3 and 4 weeks post-immersion, all sealers had similar pH values.